The Relationship between Consumer Perception and Cross-Border E-Commerce Purchase Intention among Gen Z in Penang - Lee, Zhao Seng; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2026)
Cross-Border E-Commerce (CBEC) has become more popular due to wider product choices and competitive prices. CBEC allows businesses to offer their products to global market, this will help consumers to access a wider range of products that may not be available in local markets. However Malaysian consumers still regarding low acceptance in CBEC. This is because CBEC facing high logistics costs, long delivery time, payment issues, and low trust. To examine the purchase intention in CBEC, the objective of this study is to identify the level of consumer perception (perceived usefulness, perceived ease of use, commitment and trust) among Gen Z in Penang, to identify the level of cross-border e-commerce purchase intention among Gen Z in Penang and to examine the relationship between consumer perception (perceived usefulness, perceived ease of use, commitment and trust) and cross-border e- commerce purchase intention among Gen Z in Penang. A conceptual framework was underlining theory Technology Acceptance Model (TAM) and Commitment-Trust Theory (CTT) and formed the findings of empirical studies. This study population consists of 458,500 Gen Z in Penang. Based on the population, the sample needed in this study is 384 respondents of Gen Z using snowball sampling. A quantitative research design is use and the data are collected via online questionnaires distribute to Gen Z in Penang. The response rate for this study is 62.5% which is 240 valid respondents. Data are analyse using SPSS, including pilot test, descriptive statistics, reliability analysis, normality test and correlation analysis. The results indicate that perceived usefulness, perceived ease of use, commitment and trust show positive and significant relationship with CBEC purchase intention. The findings offer insights for CBEC sellers, platform developers, and researchers to better understand how consumer perception influences purchase intention and to improve user experience on CBEC platforms.